2017
DOI: 10.1080/13880209.2017.1288750
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoids and polysaccharide peptides-enriched Ganoderma lucidum : a randomized, double-blind placebo-controlled crossover study of its antioxidation and hepatoprotective efficacy in healthy volunteers

Abstract: Context:Ganoderma lucidum (Leyss: Fr) Karst. (Polyporaceae) is an oriental medicinal fungus, commonly used in traditional Chinese medicine (TCM) for treating various condition or diseases such as hypertension, hyperglycaemia, hepatitis and cancer.Objective: The current study examines whether triterpenoids and polysaccharide-enriched G. lucidum (GL) influence antioxidation and hepatoprotective efficacy by suppressing oxidative stress.Materials and methods: Forty-two healthy subjects (22 male and 20 female) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 35 publications
0
38
0
1
Order By: Relevance
“…Furthermore, the hepatic steatosis state rate decreased through examining the hepatic enzyme activities and conducting an ultrasound. 84 Another study analyzed content of eight mushroom species and found G. lucidum to have the highest total phenolic content (TPC) (39.3±0.07 mg GAE/g), total flavonoid content (TFC) (15.1±0.04 mg GAE /g) and the strongest free radical scavenging activity (IC50=3.66 mg/mL). TPC of the other mushroom examined in the study ranged from 3.9±0.04 (Tremella fuciformis) to 11.8±0.06 (Agrocybeaegerita) mg GAE/g and TFC ranged from 0.75±0.04 (Grifolafrondosa) to 4.29±0.04 (Auricularia auricula-judae) mg GAE/g.…”
Section: Rats Exposed To 4-gy or 8-gy Radiation Dosementioning
confidence: 99%
“…Furthermore, the hepatic steatosis state rate decreased through examining the hepatic enzyme activities and conducting an ultrasound. 84 Another study analyzed content of eight mushroom species and found G. lucidum to have the highest total phenolic content (TPC) (39.3±0.07 mg GAE/g), total flavonoid content (TFC) (15.1±0.04 mg GAE /g) and the strongest free radical scavenging activity (IC50=3.66 mg/mL). TPC of the other mushroom examined in the study ranged from 3.9±0.04 (Tremella fuciformis) to 11.8±0.06 (Agrocybeaegerita) mg GAE/g and TFC ranged from 0.75±0.04 (Grifolafrondosa) to 4.29±0.04 (Auricularia auricula-judae) mg GAE/g.…”
Section: Rats Exposed To 4-gy or 8-gy Radiation Dosementioning
confidence: 99%
“…It is one of the most highly used medicinal fungi around the world [4]. Studies have shown that G. lucidum has the pharmacological effect of immunoregulation [5], antitumor [6,7], liver protection [8], and blood glucose reduction [9]. Ganoderic acid A and D ( Figure 1) are the main triterpenoids in G. lucidum [4].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Ganoderma lucidum ( G. lucidum ) exhibited preventive and therapeutic effects in cancer ( 15 ), chronic bronchitis ( 16 ), bronchial asthma ( 17 ) and hepatitis ( 18 ). Polysaccharides, which consist of glucose, mannose, galactose, xylose, fucose and arabinose, are one of the most important active components of G. lucidum ( 19 ).…”
Section: Introductionmentioning
confidence: 99%